Tagebuch eines Mannes, der Hungerturm hieß - Beck, Friedrich Alfred (Beck, 1952)
Former educator, philosopher and member of the Nazi Party interned as a security threat after the end of the war. Includes an account of his experiences as an internee in Lager Moosburg, near Munich, and Lager Staumühle, near Paderborn, along with reflections on camp conditions, Hitler, National Socialism, etc. Released on December 18, 1947.
Keywords: Autobiografie; Erlebnisbericht; Beck; Friedrich Alfred <1899->; Beck; Friedrich Alfred; Weltkrieg (1939-1945); Prisoners of war; World War; 1939-1945; Deutscher Internierter